ETIKA PROFESI POLISI - Linda Safitri; M. Fatih Al Khusni; Ulan Agung (JURNAL ILMIAH NUSANTARA, 2024)
This research will discuss what the police professional code of ethics is. Ethics comes from the Greek "ethos" which refers to a way of thinking, habits, customs, feelings, attitudes, character, moral character, or customs. Ethics can refer to a system of values ​​or values ​​and moral norms that guide individuals or groups in behaving and acting. Police Ethics is a system of values ​​or a series of moral values ​​and norms that guide the police in behaving and acting. In the Chief of Police Regulations. Republic of Indonesia Number 14. Year 2011 Concerning Professional Code of Ethics. police ethical obligations which include: State Ethics. Institutional Ethics, Community Ethics, Personality. The main duties of the Indonesian National Police are as follows: Maintaining security and public order., Enforcing the law., Providing protection, protection and assistance to the community. Therefore, it can be concluded that the legal profession, especially the police profession, in carrying out its duties has guidelines for attitudes contained in the police code of ethics law in order to create a police personality whose personality is appropriate in the eyes of the law.